Analisis Sentimen Ulasan Terkait UNESCO Global Geopark Di Google Maps dengan Algoritma Naive Bayes - Utami, Dian Siti; Erfina, Adhitia; Mupaat, M (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Ciletuh Geopark is part of the UNESCO Global Geopark Network. This study will analyze a tourist review of the Ciletuh Pelabuhan Ratu Geopark based on reviews on Google Maps. The author believes that customer reviews should be taken into consideration because they allow travelers to share their experiences. Reviews from tourists who have visited geoparks are the most important thing because these reviews can be used as information to be used as data. Because the Naïve Bayesian Algorithm is thought to have a high enough level of accuracy to identify the Unesco Global Geopark (UGG) Ciletuh Pelabuhan Ratu tourist destination that is often frequented based on visitor ratings on Google Maps, then this study utilizes it. Successively the highest accuracy values from this study were Palangpang with an accuracy value of 98.61%, Cisolok Geyser tourist attraction 94.44%, Ujung Genteng tourist attraction 98.36%, Cikaso tourist attraction 98.36%, Citepus tourist attraction 97 ,22%, Puncak Manic attractions 96.92%, Sodong attractions 95.83%, Cipanarikan attractions 95.01%, Teletubis Hill attractions 94.48%, and finally Cimarinjung attractions 94.44%.